Review of Studies on Green Accounting by Bibliometric Network Mapping Method - Killi, Mustafa; Kefe, Ilker; Isik, Yusuf (Journal of Environmental Accounting and Management, 2026)
The growing awareness of environmental issues, global warming, and the need for sustainability has prompted researchers to explore ways to integrate ecological concerns into economic systems. This study aims to identify the intellectual structure of green accounting (GA) by analyzing the bibliometric characteristics of studies in the ISI database. Using the search term "Green Accounting", a dataset of 196 studies was compiled. The research examines publication trends, citation rates, key research areas, keyword co-occurrence, and bibliographic coupling of sources, authors, and documents. The co-citation analysis of references was also conducted using VOSviewer software. Research trends were highlighted through an analysis of the Top-10 most-cited publications in GA. The results show an increasing trend in citations over the last five years, with the majority of studies focusing on business economics and environmental sciences. The most frequently used keywords are ``green accounting", ``sustainability" and ``sustainable development". The journal Ecological Economics and authors McGrath, Hynes, and McHale are identified as the most influential in bibliographic coupling, while Weitzman’s (1976) study holds the highest impact in co-citation analysis. This study contributes to understanding the development of GA by mapping its intellectual landscape and providing insights for future research. The findings provide valuable information for researchers who wish to follow the evolution of GA and the development of sustainable economic systems. This research helps to clarify the current state and future directions of GA by providing a comprehensive overview of the relevant academic literature.